2008
DOI: 10.1007/s10641-008-9341-y
|View full text |Cite
|
Sign up to set email alerts
|

Inshore migration and otolith microstructure/microchemistry of anguillid glass eels recruited to Iceland

Abstract: The timing of catches of anguillid glass eels and their otolith microstructure and microchemistry were studied in southwest Iceland, where the European eel, Anguilla anguilla and American eel, A. rostrata have been thought to live sympatrically, to learn about their early life history and the possible mechanism of the separation between these two species ranges. Catches at the site studied suggest that glass eels may have started upstream migration as the river temperature warmed in late June and early July. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…6a). These estimates agree closely with the minimum and mean number of increments observed by scanning electron micro scopy (Arai et al 2000, Wang & Tzeng 2000, Kuroki et al 2008. Our estimates matched the number of increments, but did not agree with the larval migration duration itself.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…6a). These estimates agree closely with the minimum and mean number of increments observed by scanning electron micro scopy (Arai et al 2000, Wang & Tzeng 2000, Kuroki et al 2008. Our estimates matched the number of increments, but did not agree with the larval migration duration itself.…”
Section: Discussionsupporting
confidence: 80%
“…The duration from the arrival line to estuaries was estimated as roughly 3 mo for A. anguilla (Bon hommeau et al 2009b). For A. japonica, the duration was estimated as approximately 10 d because larvae metamorphosing into glass eels were transported into the Kuroshio, which has a current speed of 1.5 m s Kuroki et al 2008). On the other hand, cohort analysis and particle-tracking models estimated a longer larval duration (>1.5 yr; Schmidt 1923, Kettle & Haines 2006, Bonhommeau et al 2009b.…”
Section: Discussionmentioning
confidence: 99%
“…Mean ages at metamorphosis for various anguillid species have been reported to range from less than a 100 days in A. celebesensis ) to almost 250 days in A. dieffenbachii (Marui et al 2001). The other tropical and temperate species of glass eels that have been examined generally have larval durations within this range (see Aoyama 2009 for a recent review), but the European eel may have a longer larval duration than any other species (see Kuroki et al 2008b). The same pattern of increment widths during metamorphosis has been observed in the Atlantic species of Conger, whose ages at metamorphosis have been estimated using this method (Correia et al 2003(Correia et al , 2004 and in a species of muraenid (Ling et al 2005).…”
Section: Aqua-bioscience Monographs Vol 2 No 4 2009mentioning
confidence: 99%
“…Powles et al (2006) showed that otoliths of ophichthid leptocephali, Myrophis punctatus, continued to deposit increments during metamorphosis, but they did not analyze increment widths. No increase in increment widths were observed in anguillid glass eels that recruited to Iceland however, which may have been due to the cold temperatures and slow metamorphosis experienced by those individuals during their leptocephalus stage (Kuroki et al 2008b). In general though, it appears that the increase in increment widths in larval eel otoliths is a useful marker for the timing of onset of metamorphosis that can be used to compare the larval durations among different eel species, as illustrated by Marui et al (2001).…”
Section: Aqua-bioscience Monographs Vol 2 No 4 2009mentioning
confidence: 99%
“…Otolith microchemistry can potentially be used to determine whether A. butcheri and the genotypically diverse array of introgressed bream spend periods of their life in the ocean (providing the opportunity for dispersal) and may indicate if bream have moved between (chemically) different estuaries (e.g. Elsdon & Gillanders 2006, Arai & Goto 2008, Bradbury et al 2008, Kuroki et al 2008, Vasconcelos et al 2008. …”
Section: Discussionmentioning
confidence: 99%